Maqashid Sharia Perspective of Legal Sanction for Khalwat Actors in Aceh - Mulizar, Mulizar; Asmuni, Asmuni; Tanjung, Dhiauddin (AL-ISTINBATH : Jurnal Hukum Islam, 2022)
This paper discusses the dynamics of punishment for khalwat perpetrators which is habitually inclined to implement the rule of law underlined in Aceh. The aim of this research is to analyze the provision of legal sanctions carried out by Acehnese for khalwat perpetrators based on the maqashid sharia perspective. This study was conducted by using empirical juridical research with law sociology approach, and the source of the main data was an interview which was completed by supporting data such as significant articles related to the khalwat cases in Aceh. The results of this study point out that normatively the provision of sanctions for khalwat perpetrators in Aceh are regulated into two forms, namely Jinayat Law Qanun, and the Development of Traditional Life and Custom Qanun. Each of these regulations has differences in the provision of law sanctions for the khalwat perpetrators that cause law dualism. Practically, the sanctions determined by Acehnese for the khalwat perpetrators are various depending on each region. There are four kinds of sanctions enforcement, namely; First: Jinayat Law Qanun, Second: Customary Law, Third: the sanction of punishment in the name of customary law, Fourth: persecution. Based on maqashid al sharia aspect, some of these punishments are considered not in accordance with sharia principles, law of persecution, and in the name of customary law. Indeed, these regulations tend to be decided arbitrarily and even followed by torture.